(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research aimed to study young people’s understanding of the concept of cybercrime, its motives, and its societal impacts in the context of digital transformation. A field study was conducted on a sample of 384 young men and women from Latakia Governorate. The study employed a descriptive-analytical approach, utilizing a questionnaire as the primary data collection and analysis tool using SPSS software. The results revealed a high level of awareness among young people regarding the concept of cybercrime, with an overall average of 4.31 and a relative importance of 86.14%. This reflects a clear understanding of the nature of these crimes, particularly those related to privacy violations (4.51) and internet misuse (4.46). The results also revealed multiple motives for committing cybercrimes, with an overall average of 3.58 and a relative importance of 71.50%. The most prominent motives were financial gain (3.90) and self-affirmation (3.74). Furthermore, the study demonstrated a high level of awareness among young people regarding the dangers of cybercrime, with an average of 4.18 and a relative importance of 83.66%. The results also showed a statistically significant correlation between understanding the concept of cybercrime and awareness of its risks (0.358), in addition to a strong correlation between the motives for committing crimes and their prevalence across digital applications (0.773).